Benchmarking best practice : excellence in rehabilitation, recovery and social reintegration for people with substance abuse problems - Helga Sif Friðjónsdóttir 1975- (2017)
According to the World Health Organization (WHO), estimated global prevalence of alcohol abuse ranges from 0%-16% and global prevalence of drug use disorders from 0%-3% for adults. There are multifaceted gains for an individual, community and society in empowering people with substance abuse disorders to make a positive change for themselves toward a life without these substances. Substance abuse treatment is accessible in Iceland and the high rates of available treatment can be considered unique worldwide. Data on the impact of substance abuse treatment in Iceland are not conclusive, however it may be stated that treatment could be further improved to better serve the needs of the users, community and society. The purpose of this study was to use a benchmarking best practice methodology to explore the fundamental treatment components of San Patrignano, a rehabilitation, recovery and social reintegration residential community for people with substance abuse problems founded in Italy in 1978. Over 70% of the residents who have completed this residential community treatment have subsequently fully integrated into society, which is an exceptional outcome. The average resident was known to be a poly-drug user who had been using for many years with severe consequences to their health, relationships and life in general. The core therapeutic processes are embedded in the day-to-day living and learning in the San Patrignano community as the rehabilitation is tailored depending on each resident´s individual needs. The services are human centered, empowerment aimed, motivational driven, educational embedded and reintegration oriented. The experience of San Patrignano could be a useful model for further development of substance abuse treatment services in Iceland.